Price relationships between qualitatively differentiated agricultural products: organic and conventional wheat in Germany. (28th January 2015) - Würriehausen, Nadine; Ihle, Rico; Lakner, Sebastian
Abstract Organic agriculture, which produces commodities that can be qualitatively differentiated from conventional food products, has grown into an important market in many countries. The dynamics of commodity prices in both sectors are partly interdependent, but are also shaped by independent determinants and have rarely been studied. We analyze organic food markets and their interdependencies with conventional markets in the context of wheat markets in Germany, which have been subject to a number of fundamental changes during the last two decades. Based on institutional market characteristics, we suggest a flexible Markov‐switching asymmetric time series model. We find a pronounced temporal sequence of market phases that differ in their asymmetric dynamics and the extent to which the organic price is influenced by the conventional price. Organic wheat prices tend to be increasingly connected to prices of conventional wheat.